Compressive Strength of Concrete Based on Slag Binder Using Pig Iron Preliminary Treatment Slag as Activator - Shin, Kyoungsu; Kim, Gyuyong; Yoon, Minho; Koo, Kyungmo (Asian Journal of Chemistry, 2015)
As a way of recycling industrial waste and reducing carbon dioxide emissions, this study has tried to improve the compressive strength of concrete that contains a large amount of fine blast furnace slag powder. To investigate the low compressive strength resulting from using a large amount of the fine blast furnace slag powder in ordinary portland cement concrete, we analyzed the concrete by measuring setting time, compressive strength, pH, SEM, EDS and XRD. A pig iron preliminary treatment slag, which is a by-product of the slag generated during the steel production process, was added based on the principle of destroying the impermeable film of the blast furnace slag powder due to the cement hydration product. As a result, it was possible to manufacture concrete with a compressive strength of 20 MPa by using 100 % industrial by-product. This was judged to affect the compressive strength by generating hydrates, such as ettringite, Ca(OH)2 and C-S-H gel, through failure of the fine blast furnace slag powder film due to the pig iron preliminary treatment slag. Also, pH and Si/Al ratio were determined to be the main factor in the development of the compressive strength.